Evaluation Geotourism Potential of Babagorgor Village Using Reynard and Pereira Methods - Amir Ali Abbaszade; Hamid Ganjaeian; Zahra Zangane Tabar; Fatemeh Noredin Mosa (جغرافیا و پایداری محیط)
Geo-sites are one of the major tourist attractions, an important role in any country's tourism industry. One of the essential strategies for the development of geotourism, is the full identification of potential areas for geotourism. Moreover, a related planning is also considered as a way to achieve the goal. At first, the site is introduced. Then, using two methods of Reynard and Pereira, the geo-sites were evaluated. After evaluating the geo-sites, their strengths and weaknesses and, the necessary strategies for the development of the region have been addressed. The findings reveal that Mineral water springs of Tangez, has the highest score. Besides, the results from multilateral evaluation along with the defined models, showed that there is no strong congruence among the geomorphological and scientific factor with management and conservation criteria. On the other hand, the models used To understand the overall stability of the region were compared in this article which explain the necessity of proposing a local model emphasizing the sustainability and the management geo-morpho-sites.